F-theory and N = 1 Quivers from Polyvalent Geometry. (1st April 2016) - Belhaj, Adil; Sedra, Moulay Brahim
Abstract: We study four-dimensional quiver gauge models from F-theory compactified on fourfolds with hyper-Kähler structure. Using intersecting complex toric surfaces, we derive a class of N = 1 quivers with charged fundamental matter placed on external nodes. The emphasis is on how local Calabi–Yau equations solve the corresponding physical constraints including the anomaly cancelation condition. Concretely, a linear chain of SU(N) groups with flavor symmetries has been constructed using polyvalent toric geometry.